2018
DOI: 10.1038/s41467-018-06056-w
|View full text |Cite
|
Sign up to set email alerts
|

An alternative pathway of enteric PEDV dissemination from nasal cavity to intestinal mucosa in swine

Abstract: Porcine epidemic diarrhea virus (PEDV) has catastrophic impacts on the global pig industry. Although the fecal–oral route is generally accepted, an increased number of reports indicate that airborne transmission may contribute to PEDV outbreak. Here, we show that PEDV could cause typical diarrhea in piglets through a nasal spray. Firstly, PEDV can develop a transient nasal epithelium infection. Subsequently, PEDV-carrying dendritic cells (DCs) allow the virus to be transferred to CD3+ T cells via the virologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
128
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(132 citation statements)
references
References 57 publications
4
128
0
Order By: Relevance
“…Airborne transmission was reported for both PEDV and PDCoV, probably via ingestion of aerosolized virus particles [71]. Recently, Li et al [73] investigated the potential mechanisms of airborne transmission of PEDV. They concluded that the virions can replicate in the nasal epithelial cells, then are carried by dendritic cells (DCs) and passed to CD3+ T cells that transport PEDV to the gut to infect intestinal cells.…”
Section: Current Opinion In Virologymentioning
confidence: 99%
“…Airborne transmission was reported for both PEDV and PDCoV, probably via ingestion of aerosolized virus particles [71]. Recently, Li et al [73] investigated the potential mechanisms of airborne transmission of PEDV. They concluded that the virions can replicate in the nasal epithelial cells, then are carried by dendritic cells (DCs) and passed to CD3+ T cells that transport PEDV to the gut to infect intestinal cells.…”
Section: Current Opinion In Virologymentioning
confidence: 99%
“…Due to its highly contagious nature, PEDV spreads rapidly through the fecal-oral route after direct or indirect exposure to infected animals or their feces [23]. PEDV may also spread through aerosolized particles [24,25]. Genetically the US PEDV strains resembled the highly virulent strains that emerged in China (China AH2012 and CH/ZMZDY/11) [5,26,27].…”
Section: Pedv: a Re-emerging Enteric Coronavirusmentioning
confidence: 99%
“…However, there is contrasting evidence regarding the ability of PEDV to productively infect DCs [67,71]. A recent study by Li et al demonstrated that PEDV can replicate in the nasal cavity and suggested that PEDV enters submucosal DCs near infected nasal epithelial cells [24]. From there, the authors purport that PEDV accessed migrating T cells, which when in peripheral blood traffic to the intestinal epithelium leading to PEDV infection of the gut [24].…”
Section: Innate Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Since December 2010, massive outbreaks of PED have occurred in China, with 80-100% morbidity and 50-90% mortality in suckling piglets (2,3). The recent research provides evidence for airborne transmission of PED virus (PEDV) (4), which has greater transmission potential than other seasonal diarrhea viruses (5,6). The small intestine, especially the jejunum and ileum, is the target tissue of PEDV infection (7).…”
Section: Introductionmentioning
confidence: 99%